Kebutuhan Modul Pembelajaran Kimia Kewirausahaan Topik Produktivitas Ikan Nila bagi Generasi Milenial - Rohman, Alif Nur; Haryani, Maefa Eka; Sari, Diah Kartika; Ad'hiya, Eka; Sofia, Sofia; W, K Anom (Jambura Journal of Educational Chemistry, 2024)
This research aims to analyze the need for a Chemistry Entrepreneurship Learning Module on the Topic of Tilapia Fish Productivity for the Millennial Generation. This research uses a qualitative descriptive method, with three stages of triangulation, there are questionnaires, interviews, and documentation. The data questionnaire was taken from student respondents in the 5th semester of the 2023/2024 academic year of the Sriwijaya University Chemistry Education Study Program. Interview data was taken from (1) students, (2) lecturers teaching entrepreneurship courses, and (3) Coordinator of the Chemistry Education Study Program. Data documentation was retrieved in the archives of data documentation was carried out in the archives at the Sriwijaya University Chemistry Education Study Program and lecturers who taught entrepreneurship courses. The researchresult show that there is a great need for chemistry learning modules with a STEM approach for entrepreneurship courses on the topic of Tilapia Fish Productivity for the Millennial Generation.